Mapping Malaysia’s poverty alleviation strategy: a typological analysis of the Malaysia Plans - Idris, Iskandar; Othman, Nooraini; Wan Zakaria, Wan Normeza (Faculty of Administrative Science and Policy Studies, 2025)
Poverty eradication remains a central priority in Malaysia’s development planning, with poverty alleviation programmes embedded in national strategies since the inception of the New Economic Policy in the 1970s. Examining how these interventions are framed within long-term planning documents is vital to understanding the strategic priorities that shape Malaysia’s evolving response to poverty. However, research on Malaysia’s poverty strategy lacks a systematic classification of programme types, limiting the ability to assess coherence, evolution, and institutional adaptation over time. This study aims to develop a typology of Malaysia’s poverty alleviation programmes by examining their representation in national development plans. The study identifies eight strategic categories and nineteen codes based on qualitative content analysis of 216 excerpts from the Second to Twelfth Malaysia Plans and their Mid-Term Reviews. These categories are analysed to reveal how Malaysia’s poverty response has shifted from structuralist models toward more individualised and empowerment-based interventions. Findings show that while infrastructure and human capital development remain dominant, recent strategies have begun incorporating microfinance, livelihood insurance, and limited social protection. Critical gaps remain, particularly in market integration, risk protection, and policy integration. The analysis also reveals strong institutional path dependency, with legacy agencies and rural-biased interventions persisting across policy eras. The typology provides a foundational lens to analyse how Malaysia’s poverty alleviation strategies have evolved across policy eras. It offers critical insights for rebalancing long-standing structural interventions with emerging needs, guiding more responsive, inclusive, and context-sensitive poverty policy development.